Problem Gambling Among Adolescents in Uganda: A Crosssectional Survey Study - Anyanwu, Michael U.; Demetrovics, Zsolt; Griffiths, Mark D.; Horváth, Zsolt; Czakó, Andrea; Bajunirwe, Francis; Tamwesigire, Imelda (Journal of Gambling Studies, 2023)
In recent years, gambling has evolved and grown substantially with new gambling activities and facilities being introduced, making gambling products and opportunities more available than ever before in Uganda. While the growth of gambling industry is considered to have a beneficial impact on the economy, it is increasingly becoming a social and public health issue especially among a minority of young people who experience problem gambling, which can damage personal, family, vocational, and academic pursuits. The present study estimated the prevalence of problem gambling and identified the socio-demographic, school, environmental and health risks of problem gambling among secondary school students in Mbarara Municipality, Uganda. A cross-sectional study was conducted among secondary school students in Mbarara Municipality. A total of 921 students from 12 schools were recruited using cluster sampling. An ordinal logistic regression model was used to explore the relationship between problem gambling and the socio-demographic, academic, environmental and health variables. Of 905 participants, 362 reported having ever gambled (40%), and 160 were classified as problem gamblers (17.7%; 44.2% among those who had ever gambled). Problem gambling was significantly associated with being male, being non-religious, other religion (African traditional religion), having employment (outside of school), distance to nearest gambling venue, parental gambling, peer gambling, substance use, risky sexual behavior, and psychological distress. The present study found a very high prevalence of problem gambling among Ugandan secondary school students. Therefore, there is need to institute public health measures towards raising awareness, prevention and treatment of problem gambling among Ugandan adolescents.
Keywords: Gambling; Adolescent gambling; Problem gambling; Adolescence; Uganda